Микроморфология интрамуральных нервов половых органов у самок голубого песца (Alopex lagopus L.) - Борусевич, В.П. (Вестник зоологии, 1971)
The nerve apparatu s of organ s wa s studied in matur e non-pregnant females of Alopex lagopus L. An analysis of the data obtained showed that in uterus and vagina walls there are an advenlitious-serous, intermuscular and mucous plexuses consisting of myelinated and non-myelinaled nerve fibres, various nerve endings and cells of type I and II by Dogel located in ganglia . The reactive change s lake place in nerve fibres ol the ovary, in some fibres the processes of degeneration arc observed. It is connected probably with complex processes of morpho-functional rearrangement of the organ at sex rest. The data obtained testify to abundant innervation of sex organ s in females of Alopex lagopus L.